A Grammar of Khowar: Descriptive and comparative analysis - Bashir, Elena (Grammars of World and Minority Languages, 2025)
This book is the first full-length English-language grammar of Khowar, one of the Far Northwestern Indo-Aryan languages. It reflects more than 30 years of field research by the author, and attempts to capture a snapshot of the language at the end of the twentieth century, a time when this and other small mountain languages in northern Pakistan were undergoing rapid change, the pace of which continues to accelerate. An introductory chapter presents the language in its genetic, geographical, and typological contexts, and its multi-layered lexicon. There follow chapters on phonology, word formation and derivational morphology, nominal morphology, deictic elements, the verbal system, adjectival modification, adverbial modification, morphosyntax, and morphosemantics. This final chapter is a distillation of features of the language that are central to understanding how it conceives of and portrays the world. In addition to grammatical analysis and discussion, A Grammar of Khowar features numerous original example sentences, mostly contributed by senior, highly competent speakers of the language. A significant number of examples are drawn from oral texts recorded by the author in several villages. They are presented in roman representation and are accompanied by a complete morphological analysis and English translation. Additionally, an Appendix contains a 30-page sample text, presented first in Khowar’s Perso-Arabic script then by roman-based morphological analysis and an English translation by the author.